Pancasila sebagai sistem etika: landasan pendidikan karakter, kebijakan publik, dan kontribusi global - Hakim, Moh Zaki Aulia (Maliki Interdisciplinary Journal, 2026)
This study examines Pancasila as an ethical system in shaping the character of the Indonesian nation. Pancasila is not merely a political ideology but also a moral compass that guides the behavior of society in national and civic life. The values embedded in each principle of Pancasila form a comprehensive ethical framework, encompassing spirituality, humanity, unity, democracy, and social justice. In the context of education, Pancasila serves as the foundation for developing young generations who are religious, virtuous, independent, and democratic. However, in the era of globalization and digitalization, Pancasila’s values face serious challenges such as moral crises, identity degradation, and social polarization. Therefore, the internalization of Pancasila’s values is urgently needed in formal education, public policy, and social life. This study emphasizes that Pancasila has universal relevance, functioning not only as a unifying force for the nation but also as Indonesia’s contribution to global civilization